IMPROVEMENT OF ORTHOPEDIC CARE FOR PATIENTS WITH EXTRAORAL PATHOLOGY UNDERGOING RADIATION THERAPY - Ravshanova N. A. (The Conference Hub, 2025)
To enhance the quality of life of patients who have undergone extensive oncologic procedures in the maxillofacial region, a staged prosthetic treatment approach is implemented. The development of materials that more closely resemble living tissue has driven significant advancements in the field of facial prosthetics in recent decades. These materials encompass siloxanes. The Central Scientific Research Institute of Prosthetics has conducted experimental and clinical studies that have demonstrated that silicone prostheses are biologically inert, maintain their shape, and retain their elasticity and strength [2]. Rapid prototyping and three-dimensional modelling technologies are currently being actively implemented.
Keywords: rehabilitation, oncology, maxillary defect, combined defects, formative prosthesis, facial prostheses